AI-Generated Art: Copyright, Creativity, and Ethical Ownership (Journal of responsible AI & ethics, 2026)
The rapid advancement of artificial intelligence has transformed the landscape of artistic production. AI-generated art, created through machine learning algorithms such as generative adversarial networks (GANs) and diffusion models, has raised fundamental questions regarding creativity, copyright ownership, and ethical responsibility. Unlike traditional art forms, AI art involves collaboration between human input, algorithmic processes, and large datasets that often contain copyrighted materials. This situation has generated significant debates among artists, legal scholars, policymakers, and technologists regarding the legitimacy of AI-generated content as intellectual property and the ethical implications of using data sourced from existing artworks. This paper explores the evolving relationship between artificial intelligence and creative expression by examining how AI-generated art challenges traditional definitions of authorship and ownership. The study investigates copyright frameworks across different jurisdictions and analyzes how legal systems interpret AI-produced works in the context of intellectual property law. Furthermore, it examines the ethical dilemmas associated with dataset training, artistic attribution, and the commercialization of AI-generated creative outputs.